Computational Analysis of Oxide Ion Conduction in Orthorhombic Perovskite Structured La(0.9)A(0.1)InO(2.95) (A = Ca, Sr and Ba) - Yoon, Mi-Young; Hwang, Kuk-Jin; Byeon, Dae-Seop; Kim, Joosun; Hwang, Hae-Jin; Jeong, Seong-Min (WILEY, 2015)
Oxide ion conduction in orthorhombic perovskite structured oxides, La(0.9)A(0.1)InO(2.95) (A=Ca, Sr and Ba) is analyzed using molecular dynamics simulation. Factors influencing oxide ion conductivity of the compositions considered are analyzed using radial distribution function, bond energies between dopant and oxide ions, and the diffusion path. It is known that perovskite oxides with smaller ion size mismatch between host and dopant ions have higher electrical conductivities. However, exceptions exist, such as a La(0.9)A(0.1)InO(2.95) (A=Ca, Sr and Ba) system, where high electrical conductivities occur with large ion size mismatches. Based on this study, a dopant with smaller ion than host ion results in the formation of strong ionic bonds with oxide ions, suggesting that the A-site dopant should be larger than the host ion for forming weaker O-A bonds. Consequently, the trade-off between ion size mismatch and O-A bond needs to be considered for enhancing oxide ion conductivity of perovskite oxides.
Keywords: MOLECULAR-DYNAMICS SIMULATION; YTTRIA-STABILIZED ZIRCONIA; DOPED SRTIO3; DIFFUSION; TRANSPORT; LAINO3